Pengaruh kepemimpinan demokratis, lingkungan, dan disiplin terhadap kinerja pegawai non ASN di sekretariat DPRD Kabupaten Badung tahun 2023 - Dewa Ayu Ratih Adhi Pratiwi; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani; Luh Riniti Rahayu (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: This study aims to determine and analyze the influence of democratic leadership, the work environment, and discipline on the performance of non-ASN employees at the Badung Regency DPRD Secretariat. Research methodology: This research methodology is quantitative research. The data collection technique involved a survey using a questionnaire with a total sample of 73 non-ASN employees. Data analysis was performed using the SmartPLS software. Results: The findings showed that the t-count value determined for the variable “Democratic Leadership” was greater than the t-table value (12.292 > 1.6). The t-count value of the working environment variable is greater than the t-table value (7.084 > 1.6). The t-count value of the identified work discipline variable is greater than the t-table value (12.218 > 1.6). Therefore, democratic leadership has a positive impact on employee performance, the work environment has a real positive impact on employee performance, work discipline has a real positive impact on employee performance, and at the same time democratic leadership (X1), work environment (X2), and work discipline (X3) have a significant (real) impact on employee performance (Y). If these three variables increase together, the performance of non-ASN employees in the Badong County Regional Representative Committee Secretariat will also increase. Limitations: The sample used in this research was a saturated sample of 73 non-ASN employees at the Badung Regency DPRD Secretariat, so the possibility of obtaining different results cannot be ruled out if a research model and a larger number of samples were used. Contribution: This research is expected to provide additional information or input in an effort to improve the performance of non-ASN employees at the Badung Regency DPRD Secretariat.